Colour Removal of Synthetic Wastewater by Using Biomaterials - Manogaran, S.; Sulochana, N.; Chitravel, M. (Asian Journal of Chemistry, 2016)
A carbonaceous sorbent prepared from an indigenous agricultural waste Operculina turpethum (Convolvulaceae), Trianthema pentandra (Asclepiadaceae) and Hemidesmus indicus (Aizoaceae) by acid treatment, was tested for the colour removal of industrial wastewater. In the present study, the roots of the above mentioned biomaterials were used to remove the colour of synthetic wastewater prepared by using analytical grade potassium permanganate, potassium dichromate and chromium sulphate chemicals. The results indicate that biomaterials are highly useful ones.